PROFIL REPRESENTASI MATEMATIS SISWA PADA MATERI BANGUN RUANG SISI DATAR DI SMP NEGERI 02 BARAS: Profile of Student’s Mathematical Representation of Geometry Flat Side at Smp Negeri 02 Baras - Datuanggoa, Jeniati; Bennu, Sudarman; Pathuddin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
This study aims to describe the mathematical representation of geometry flat  side at SMP Negeri 02 Baras. This type of research is qualitative research. The subjects of this study were grade IX students of SMP Negeri 02 Baras which consisted of one student with high math ability and one student with low math ability. Collecting data by giving assignments and interviews. The results of this study are: (1) Students' mathematical representation on visual representation for students with high mathematical abilities to solve problems by making pictures of geometric patterns to clarify and facilitate completion, students with high mathematical abilities make geometric patterns according to the problem given, namely drawing cubes and pyramids, while students with low math skills do not draw geometric patterns to clarify and facilitate completion. (2) Students' mathematical representation on symbolic representation for students with high and low mathematical abilities to solve problems involving mathematical expressions, namely determining the formula used using mathematical symbols and performing number operations correctly. (3) The students' mathematical representation on the verbal representation for students with high mathematical abilities explains the steps for solving mathematical problems in written and oral texts, while students with low mathematical abilities are still wrong in determining the steps for solving them.